2016
DOI: 10.1128/mcb.00785-15
|View full text |Cite
|
Sign up to set email alerts
|

The Mediator Subunit MED16 Transduces NRF2-Activating Signals into Antioxidant Gene Expression

Abstract: The KEAP1-NRF2 system plays a central role in cytoprotection. NRF2 is stabilized in response to electrophiles and activates transcription of antioxidant genes. Although robust induction of NRF2 target genes confers resistance to oxidative insults, how NRF2 triggers transcriptional activation after binding to DNA has not been elucidated. To decipher the molecular mechanisms underlying NRF2-dependent transcriptional activation, we purified the NRF2 nuclear protein complex and identified the Mediator subunits as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
69
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
3
2

Relationship

2
8

Authors

Journals

citations
Cited by 76 publications
(74 citation statements)
references
References 37 publications
(43 reference statements)
3
69
0
Order By: Relevance
“…pGEX4T-1 mNRF2 mutant vectors expressing GST and GST-NRF2 mutants were used for recombinant protein production (22). For a reporter assay and protein expression in HEK293T cells, pRBGP2 (3ϫ ARE-LUC), pRBGP4 (3ϫ mut ARE-LUC), p3xFLAG-NRF2, pcDNA3-FLAG-hGR␣, and pRL-LUC (internal control) were used (39,40).…”
Section: Plasmidsmentioning
confidence: 99%
“…pGEX4T-1 mNRF2 mutant vectors expressing GST and GST-NRF2 mutants were used for recombinant protein production (22). For a reporter assay and protein expression in HEK293T cells, pRBGP2 (3ϫ ARE-LUC), pRBGP4 (3ϫ mut ARE-LUC), p3xFLAG-NRF2, pcDNA3-FLAG-hGR␣, and pRL-LUC (internal control) were used (39,40).…”
Section: Plasmidsmentioning
confidence: 99%
“…Very recently, it has been reported that Nrf2 directly interacts with the subunit MED16 of the Mediator complex. Given that the association Nrf2-MED16 does not affect Nrf2 binding to the ARE, and that MED16 can recruit and/or activate RNA Polymerase II, the interaction Nrf2-MED16 is crucial for connecting stress signals to the transcriptional apparatus [72].…”
Section: Positive Regulatorsmentioning
confidence: 99%
“…The tail has also been reported to be dispensable for Mediator occupancy at TFIID-dominated genes (39), though this has recently been questioned (34). One possible mechanism for recruitment of Mediator to sn/snoRNAs is via the interaction of activators, including Tbf1, with other subunits of Mediator, such as the tail/middle module connector Med16, which interacts with activators such as Gcn4 in yeast (49), DIF in Drosophila (53), and NRF2 in mouse and human (54). Indeed, a recent proteomic analysis of Mediator interactions reported a modest interaction between Mediator and Tbf1 (55).…”
Section: Discussionmentioning
confidence: 99%